(untitled) (Historia, 2021)
The meaning of history is a subject that historians tend to address at crucial intervals. It is also as if the historian as philosopher or the philosopher as historian needs to take account of the world and the discipline. In his motivation for considering the meaning of history, the eminent German philosopher of history, Jörn Rüsen, states that it is important to contemplate the experience of catastrophe that was the order of the day in the twentieth century. Much of the disciplinary certainties that prevailed have been eroded in the methodology of history because of the fashionable cultural turn following the experiences of shock and disbelief encountered in the past century. The work then unfolds in two distinct sections. The first deals with meaning and the larger more comprehensive second section with the metaphorical Schritte ins Niemandsland (Steps in no man’s land). In the epiloque there is a rational evaluation by the historian as philosopher of the ludicrous assumptions of attaching special meaning to time at the turn of the millennium.